Prevalence and Severity of Demodex folliculorum and Demodex brevis Infestation and their Association with Common Skin Diseases in Northwest Iran - Milad Afşar; Khosrow Hazrati Tappeh; Yunus Emre Beyhan (Journal of Arthropod-Borne Diseases)
Background: Demodex spp., a cosmopolitan mite, can exist as a commensal or parasitic organism. This study aimed to investigate the prevalence of Demodex spp. infestation in patients with common skin diseases and explore the potential association between demodicosis and these conditions in Urmia, northwest Iran.